Financial Performance and Technical Efficiency Differentials for Apicultural Technologies in Nakaseke District, Uganda - Kalule, Stephen W.; Ssebbale, Edrisa (The Journal of Developing Areas, 2014)
Despite apiculture being potentially a large income earner, the financial performance apicultural technologies at farm-level is still poor yet very few studies have delved in Using a representative sample of 69 respondents from Nakaseke District, the Ordered revealed that farming experience, apiary plot size, shortness of distance of water source colonization levels were the major positive determinants of apicultural financial Stochastic Frontier Analysis (SFA) suggested that 62% and 76% of the total variation output in traditional and improved technologies was due to technical inefficiency. efficiency levels in traditional technology seemed to suggest that more honey output realized through introduction of improved technologies rather than focusing on technical the low efficiency in improved technology would be improved using technical training. recommended policy incentives ranging from specific commodity-targeting extension provision of low interest rate credit products and baiting materials
Keywords: Apicultural technologies; Production elasticities; Technical